A contribution to the study of the urbanization of today's old core of Zemun during the 18th century - Mićović Nela (Nasleđe)
During the redevelopment of Zemun's main street in 2023, a terracotta tablet measuring 43x28x6 cm was discovered in the process of excavations for a telecommunications shaft, at an elevation of 76.88. On the front of this was etched an inscription in Latin mentioning the name Johannes Radmacher, his official title, and the year 1776. An analysis of archival materials and cartographic plans confirmed that the tablet belonged to a house in Glavna Ulica (Main Street) (today's number 15), where, according to the Zemun Magistrate's censuses, Johannes Radmacher lived from 1773 to 1787. This house was damaged in the bombing of 1944 and later demolished, with the Beograd department store being built in its place. The remains of a brick sewer were discovered along the entire street, with this having been built in the 18th century, and remaining in use until the construction of the modern sewage system. The archeological finds discovered have both documentary and historical value, and justify a brief summation, as a witness to the urbanization of what is today deemed Zemun's historic core during the 18th century.